An Economic Critique of Current Technological Change Displacement Techniques - Ross, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
This study attempts to assess how effective are the present methods employed by private parties for adjusting workers to technological change ; and effective is defined on the basis of the loss that displaced workers are expected to incur. The major conclusion is that if provisions such as advance notice, severance pay, attrition, seniority and bumping, early retirement, reduced work week, joint committees, and retraining are performing effectively it is largely the result of luck and circumstance